992. Oral Ibrexafungerp Outcomes in Patients with Oropharyngeal and Esophageal Candidiasis from an Interim Analysis of a Phase 3 Open-label Study (FURI). (4th December 2021) - Vazquez, Jose A; Cornely, Oliver; Koehler, Philipp; Rautemaa-Richardson, Riina; Bazaz, Rohit; Marshall Lyon, G; Marty, Francisco M; Gonzalez-Bocco, Isabel H; Miller, Rachel; Walsh, Thomas J; Pappas, Peter; McCarty, Todd P; et al.
Abstract: Background: Candida albicans is the predominant organism causing esophageal candidiasis (EC) and oropharyngel candidiasis (OPC). These infections may arise from subjects colonized with Candida who are predisposed due to illness, debility or a local reduction in host resistance to an overgrowth of their own indigenous flora. Patients with mucocutaneous Candida infections can be treated in the outpatient setting, yet there are limited oral treatment options available for patients who are unresponsive to or who are intolerant to currently available antifungals. Oral ibrexafungerp is an investigational broad-spectrum glucan synthase inhibitor antifungal with activity against Candida species, including azole- and echinocandin-resistant strains. A Phase 3 open-label, single-arm study of ibrexafungerp (FURI; NCT03059992) is ongoing for the treatment of patients intolerant of or with fungal disease refractory to standard antifungal therapy. Table 1. FURI Outcomes in OPC and EC Methods: FURI subjects were eligible for enrollment if they had proven or probable severe mucocutaneous candidiasis, invasive candidiasis, invasive aspergillosis, or other fungal diseases with evidence of treatment failure, intolerance, or toxicity related to a currently approved standard-of-care antifungal treatment or if they were unable to receive an approved oral antifungal option (e.g., susceptibility of the organism) and a continued IV antifungal therapy was clinically undesirable or unfeasible. Results: An independent Data Review Committee (DRC) provided an assessment of treatment response for 74 subjects enrolled in the FURI study from 22 centers in US, UK and EU treated with ibrexafungerp for mucocutaneous or invasive fungal infections from 2016- 2020. A total 32 subjects (43.2%) had mucocutaneous candidiasis and 24 subjects were diagnosed with OPC or EC. The percent of patients who were determined to have a complete response (CR) or partial response (PR) was 62.5%, stable disease (SD), 20.8%, and progression of disease, 16.7%. Table 1 shows outcomes by EC and OPC as determined by the DRC. Conclusion: Analysis of 24 EC and OPC patients from the FURI study indicates that oral ibrexafungerp provides a favorable therapeutic response in patients with challenging mucocutaneous fungal disease and limited treatment options. Disclosures: Oliver Cornely, Prof., Actelion (Consultant, Grant/Research Support)Al-Jazeera Pharmaceuticals (Consultant)Allecra Therapeutics (Consultant)Amplyx (Consultant, Grant/Research Support)Astellas (Consultant, Grant/Research Support)Basilea (Consultant, Grant/Research Support)Biocon (Consultant)Biosys (Consultant)Cidara (Consultant, Grant/Research Support)CoRe Consulting (Consultant)Da Volterra (Consultant, Grant/Research Support)DFG (German Research Foundation ) (Grant/Research Support)Entasis (Consultant)F2G (Consultant, Grant/Research Support)German Federal Ministry of Research and Education (Grant/Research Support)Gilead (Consultant, Grant/Research Support)Grupo Biotoscana (Consultant)Immunic (Grant/Research Support)IQVIA (Consultant)Janssen (Grant/Research Support)Matinas (Consultant)Medicines Company (Grant/Research Support)MedPace (Consultant, Grant/Research Support)Melinta Therapeutics (Grant/Research Support)Menarini (Consultant)Merck/MSD (Consultant, Grant/Research Support)Molecular Partners (Consultant)MSG-ERC (Consultant)Mylan (Consultant)Nabriva (Consultant)Noxxon (Consultant)Octapharma (Consultant)Paratek (Consultant)Pfizer (Consultant, Grant/Research Support)PSI (Consultant)Roche Diagnostics (Consultant)Scynexis (Consultant, Grant/Research Support)Seres (Consultant)Shionogi (Consultant)Wiley (Blackwell ) (Other Financial or Material Support) Philipp Koehler, MD, Ambu GmbH (Consultant, Speaker's Bureau)Astellas Pharma (Speaker's Bureau)Euopean Confederation of Medical Mycology (Speaker's Bureau)German Federal Ministry of Research and Education (Grant/Research Support)Gilead (Consultant, Speaker's Bureau)MSD (Speaker's Bureau)Noxxon N.V. (Consultant)Pfizer (Speaker's Bureau)State of North Rhine-Westphalia, Germany (Grant/Research Support) Riina Rautemaa-Richardson, DDS, PhD, FRCPath, SCYNEXIS, Inc. (Scientific Research Study Investigator) G. Marshall Lyon, MD, SCYNEXIS, Inc. (Scientific Research Study Investigator) Francisco M. Marty, MD, SCYNEXIS, Inc. (Scientific Research Study Investigator) Rachel Miller, MD, SCYNEXIS, Inc. (Scientific Research Study Investigator) Thomas J. Walsh, MD, PhD (hon ), Scynexis (Consultant, Grant/Research Support)Shionogi (Consultant, Grant/Research Support) Peter Pappas, MD, Astellas (Grant/Research Support)Cidara (Grant/Research Support, Advisor or Review Panel member)Mayne (Grant/Research Support, Advisor or Review Panel member)Merck (Grant/Research Support)SCYNEXIS, Inc. (Consultant, Grant/Research Support) Todd P. McCarty, MD, Cidara (Grant/Research Support)GenMark (Grant/Research Support, Other Financial or Material Support, Honoraria for Research Presentation)T2 Biosystems (Consultant) Caryn Morse, MD, Chimerix (Scientific Research Study Investigator)Covis Pharma (Scientific Research Study Investigator)Gilead Sciences Inc. (Scientific Research Study Investigator)Ridgeback Biotherapeutics (Scientific Research Study Investigator)Roche (Scientific Research Study Investigator)SCYNEXIS, Inc. (Scientific Research Study Investigator)Theratechnologies (Advisor or Review Panel member)Viiv (Advisor or Review Panel member) Luis Ostrosky-Zeichner, MD, Amplyx (Consultant)Cidara (Consultant)F2G (Consultant)Gilead (Grant/Research Support, Speaker's Bureau)Pfizer (Scientific Research Study Investigator, Speaker's Bureau)Scynexis (Grant/Research Support, Scientific Research Study Investigator)Viracor (Consultant) Jürgen Prattes, Dr, AbbVie Inc. (Shareholder)Gilead (Speaker's Bureau)MSD (Grant/Research Support)Novo Nordisk (Shareholder)Pfizer (Advisor or Review Panel member)Stryker (Shareholder) Andrej Spec, MD, MSCI, SCYNEXIS, Inc. (Consultant, Scientific Research Study Investigator) David Andes, MD, SCYNEXIS, Inc. (Scientific Research Study Investigator) Oliver Witzke, MD, SCYNEXIS, Inc. (Scientific Research Study Investigator) Nkechi Azie, MD, SCYNEXIS, Inc. (Employee, Shareholder) David A. Angulo, MD, SCYNEXIS, Inc. (Employee, Shareholder)